(untitled) (The Pakistan Development Review, 2003)
Globalisation describes the increasing integration of national economies through international trade, capital transfers, and the exchange of information or knowledge. This paper focuses exclusively on trade integration. Most economists hold that reducing trade barriers has a decisive positive effect on economic growth and poverty reduction (“openness hypothesis”). However, some economists diagnose deficient or weakly enforced non-market institutions as the major cause of slow growth. The main goal of this paper is to show that these two seemingly contrary points of view do not exclude each other. Openness is not only influenced by trade policy but also by other policies and the quality of institutions. Available data show a high negative correlation between the logarithm of tariff rates and indicators of the quality of institutions. Cross-national growth regressions demonstrate that the explanatory power of trade protection and a combined measure of openness, on the one hand, and institutional quality, on the other hand, is comparable. Therefore, it is concluded that liberal trade policies are recommendable, but must be complemented by sound macroeconomic management, micro-policy to strengthen domestic competition, and institutional improvements.